PENDEKATAN TASK CENTERED SYSTEM DESIGN PADA SISTEM INFORMASI PENYEWAAN GEDUNG SERBAGUNA - Tiara Sabni Hidayah; Hengky Anra; Helen Sastypratiwi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Multipurpose venue rentals in Pontianak are still largely handled manually, leading to inaccuracies in schedules, room availability, and transactions. This study designs and evaluates a web-based rental information system UI/UX using the Task-Centered System Design (TCSD) approach. The four TCSD stages identification, user-centered requirement analysis, design as scenario, and walkthrough evaluate were applied to map key user tasks (T1–T6), build user flows, and produce a high-fidelity Prototype. Usability was assessed with Maze remote testing and the System Usability Scale (SUS) on 15 participants. Results show a Maze usability score of 96 (High) and an average SUS score of 81.3 (Excellent), indicating that the Prototype is easy to learn, consistent, and effective. A relatively higher mis-click rate (21.1%) on package-selection highlights opportunities to refine selection controls and calendar affordances.